Amisulpride prevents nausea and vomiting associated with highly emetogenic chemotherapy: a randomised, double-blind, placebo-controlled, dose-ranging trial - Herrstedt, Jørn; Jordan, Karin (Supportive care in cancer, 2019)
Purpose Chemotherapy-induced nausea and vomiting (CINV) remain significant clinical problems, especially in the delayed phase (24-120 h after chemotherapy). Amisulpride is a dopamine D2/D3-receptor...
First online: 28 November 2018
Gesehen am 22.07.2019